2015
DOI: 10.3329/fmcj.v9i1.23618
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of imprint cytology and frozen section for CNS tumor

Abstract: :The present study was a cross-sectional type of descriptive one carried out with the objective of determining the diagnostic accuracy of imprint cytology and frozen section of central nervous system tumors. A purposively selected sample of 33 clinically diagnosed patients with CNS tumors has been included for the study. The relevant data on CNS tumors were collected by using imprint cytology, frozen section and paraffin section. The sensitivity of imprint cytology was 75.0% and specificity was 55.17% respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 1 publication
(1 reference statement)
2
4
0
Order By: Relevance
“…Based on our study, there was no significant difference in diagnostic accuracy of cytology smear and frozen section as both techniques revealed comparable and high diagnostic accuracy. Other studies also conclude similar findings (Ahmed et al, 2015;Nanarng et al, 2015;Louis and von Deimling, 2017;Agrawal et al, 2014). This provide an alternative solution to the centres that are lack frozen section facilities and skills.…”
Section: Difference In the Proportion Of Accuracy Between Cytology Smsupporting
confidence: 64%
See 1 more Smart Citation
“…Based on our study, there was no significant difference in diagnostic accuracy of cytology smear and frozen section as both techniques revealed comparable and high diagnostic accuracy. Other studies also conclude similar findings (Ahmed et al, 2015;Nanarng et al, 2015;Louis and von Deimling, 2017;Agrawal et al, 2014). This provide an alternative solution to the centres that are lack frozen section facilities and skills.…”
Section: Difference In the Proportion Of Accuracy Between Cytology Smsupporting
confidence: 64%
“…The sample size was calculated using the estimation of sensitivity and specificity sample size calculator by Dr Lin Naing@Mohd Ayub Sadiq from School of Dental Sciences, USM. The estimated sample size to answer the objectives was 48 calculated based on the expected sensitivity and specificity were 100% and 86.21% respectively (Ahmed et al, 2015). This study was approved by the Human Research Ethics Committee, USM with the reference USM/JEPeM/18010083.…”
Section: Case and Sample Selectionmentioning
confidence: 99%
“…20 Our 3.31% false-negative results agree with those reported elsewhere. 18,19,[21][22][23][24] Studies have shown that pathologists using IC obtain a high diagnostic accuracy which rivals that of FS, ranging from 60% to100%, depending on the specimen type. 1,4,5,13,25 Our findings of 91.6% sensitivity, 97.7% specificity, 94.1% PPV, and 96.7% NPV support the notion that IC is highly accurate in the evaluation of primary or metastatic disease.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, all the six CNS cases were accurately diagnosed by frozen section and imprint cytology. SAM Ahmed et al, [25] studied 33 clinically diagnosed patients of CNS tumours, and the sensitivity of frozen section was 100% and that of imprint cytology was 75%. The accuracy of both the techniques in our study were comparable to this study.…”
Section: Discussionmentioning
confidence: 99%